How important is tryptophan in human health?. Issue 1 (2nd January 2019) - Kałużna-Czaplińska, Joanna; Gątarek, Paulina; Chirumbolo, Salvatore; Chartrand, Max Stanley; Bjørklund, Geir
ABSTRACT: Tryptophan (Trp) is an amino acid and an essential component of the human diet. It plays a crucial role in many metabolic functions. Clinicians can use Trp levels in the course of diagnosing various metabolic disorders and the symptoms associated with those diseases. Furthermore, supplementation with this amino acid is considered in the treatment of depression and sleep disorders, mainly due to the Trp relationship with the synthesis of serotonin (5-HT) and melatonin. It is also used in helping to resolve cognitive disorders, anxiety, or neurodegenerative diseases. Reduced secretion of serotonin is associated with autism spectrum disorder, obesity, anorexia and bulimia nervosa, and other diseases presenting peripherals symptoms. The literature strongly suggests that Trp has a significant role in the correct functionality of the brain-gut axis and immunology. This information leads to the consideration of Trp as an essential dietary component due to its role in the serotonin pathway. A reduced availability of Trp in diet and nutraceutical supplementation should be considered with greater concern than one might expect. This paper constitutes a review of the more salient aspects gleaned from the current knowledge base about the role of Trp in diseases, associated nutritional disorders, and food science, in general.